2019
DOI: 10.1002/slct.201903385
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Corn (Zea mays L. var. rugosa) Derived Fluorescent Carbon Quantum Dots for Selective Detection of Hydrogen Sulfide and Bioimaging Applications

Abstract: We report a green, simple, and facile fluorometric method for the detection of hydrogen sulfide (S 2À ) using bluish green carbon quantum dots (CQDs) derived from sweet corn (Zea mays L. var. rugosa) as carbon source. The optical properties of the CQDs were studied using UV-visible, PL spectra and lifetime measurements. High-resolution transmission electron microscopy (HR-TEM), atomic force microscope (AFM) and dynamic light scattering (DLS) were used for morphological studies. Xray diffraction (XRD) technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…The strong characteristic absorption of GQDs prepared from grape seeds [ 109 ] as carbon source was recorded near 220 and 290nm (Figure 6A), which was caused by π‐π * transition and n‐π * transition caused by sp 2 aromatic structure, respectively. [ 110,111 ] The CQDs prepared by sweet corn [ 9 ] had an absorption peak at 260 nm, which belongs to the π‐π* transition caused by C = C bonds and the n‐π* transition caused by C = O bonds. The N‐CQDs synthesized by Lu et al [ 112 ] from watermelon juice had obvious absorption at 282nm and weaker than that at 355nm, which was attributed to the π ‐ π * transition caused by C = C or C = N bonds and the n‐π * transition of C = O bonds, respectively (Figure 6B).…”
Section: Basic Characterization and Properties Of Biomass Carbon Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong characteristic absorption of GQDs prepared from grape seeds [ 109 ] as carbon source was recorded near 220 and 290nm (Figure 6A), which was caused by π‐π * transition and n‐π * transition caused by sp 2 aromatic structure, respectively. [ 110,111 ] The CQDs prepared by sweet corn [ 9 ] had an absorption peak at 260 nm, which belongs to the π‐π* transition caused by C = C bonds and the n‐π* transition caused by C = O bonds. The N‐CQDs synthesized by Lu et al [ 112 ] from watermelon juice had obvious absorption at 282nm and weaker than that at 355nm, which was attributed to the π ‐ π * transition caused by C = C or C = N bonds and the n‐π * transition of C = O bonds, respectively (Figure 6B).…”
Section: Basic Characterization and Properties Of Biomass Carbon Dotsmentioning
confidence: 99%
“…In fact, low‐cost biomass, which is considered to be waste, have been converted into valuable carbon dots by some researchers due to its advantages of renewable, low pollution, and wide distribution. In recent years, researchers have used biomass such as plants and their derivatives, [ 4–10 ] animals their derivatives [ 11–14 ] and municipal waste [ 15–17 ] to produce biomass carbon dots (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…While endosomal escape represents a daunting challenge in the field, many studies have suggested potential solutions for effective release of nanoparticles inside cells. 71,72 Much progress has been made in subcellular targeting of nanoparticles within the context of drug delivery, 73 as well as medical applications-especially for oncology (e.g., thermal ablation of tumor cells). 74 Efforts include surface modifications, bioconjugate reactions, 75 and hybridization of different nanocomponents including, but not limited to, liposomes, micelles, mesoporous silica, polymers, viruses, AuNPs, and carbon nanotubes.…”
Section: Outlook For Future Intracellular Modulationmentioning
confidence: 99%
“…CDs possess the exceptional PL properties in colloidal phase and widely used in various solution phase sensing systems. [13][14][15][16][17][18] However, there are few work involving latent fingerprint detection by CDs in solid state because of aggregation-induced quenching effects during drying. [19] Recently, by mixing of the CDs with polymer followed by solvent evaporation, fluorescent CD-based nanocomposite films or gel glasses were obtained, [20][21][22][23] in which the polymer acted as a matrix and suppressed the aggregation of CDs in solid state.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent carbon nanodots (CDs), a new member of nanoparticle family have drawn attention owing to their high photoluminescence (PL), good biocompatibility, low cost and low toxicity over the past decade, which make fluorescent CDs a very promising alternative to traditional fluorescent materials. CDs possess the exceptional PL properties in colloidal phase and widely used in various solution phase sensing systems . However, there are few work involving latent fingerprint detection by CDs in solid state because of aggregation‐induced quenching effects during drying .…”
Section: Introductionmentioning
confidence: 99%